Synergizing for social impact: empowering community diabetes management through low- carb diet education book to aid in better glycaemic control under medical supervision - Mohd Ismail, Nafeeza; Ab Azis, Norasikin; Kamarudin, Siti Norsyafika; Razali, Norhafiza; Haron, Mohammad Huzaimi; Md Yasin, Mazapuspavina; Abdul Malik, Khasnur; Ismail, Ilham Ameera; Ismail, Nazrul Hadi; Abu Hanipah, Noor Fahitah (Universiti Teknologi MARA, Kedah, 2024)
The prevalence of Type 2 Diabetes Mellitus (T2DM) poses significant health challenges worldwide and Malaysia is not spared. Effective management strategies are essential to improve glycaemic control and reduce complications. This project addresses the need for practical, accessible educational resources for T2DM patients in the community by developing and validating a comprehensive book that serves as an educational tool and guide for those adopting a lowcarbohydrate approach under medical supervision. The objective was to develop a validated educational book to aid T2DM patients in better glycaemic control through a low-carb diet which would aid the community and doctors. The book has seven key chapters covering the introduction to T2DM, understanding macronutrients, identifying different names of sugar, evaluating sugar content, reading nutrition labels, initiating a low-carb diet, and providing easy low-carb recipes. The content was developed based on current scientific research and validated through expert reviews and feedback. Feedback from medical experts and dietitians indicated that the book is a comprehensive, user-friendly resource. Experts praised the book for its clear, concise information and practical guidance, making it a valuable tool for patients. The validation process confirmed the book’s potential to improve patient knowledge and support dietary adherence. In conclusion, the book represents a novel validated educational tool specifically tailored for T2DM patients, focusing on a low-carb dietary approach and providing a structured, easy-to-understand format. This resource hopes to contribute to significant social impact, promoting healthier lifestyles and foreseeable cost savings from reduced medication use and fewer diabetes-related complications.